A Comparison Study on the Effect of Cooperative Teaching Learning and Problem Based Learning Methods on the Level of Academic Performance Among Year 2 and Year 3 General Nursing Diploma Students at Oman Nursinginstitute, Muscat - Lakshmi, L. (2018)
Cooperative Teaching Learning (CTL) and Problem Based Learning (PBL) are the innovative methods which potentially help the student to learn more effectively and to make teaching learning process student friendly. Regardless of widespread evidences representing that these two methods improve academic performance, there are very few studies conducted in nursing education. There is lack of research about the utilization of the above-mentioned innovative teaching methods in Oman.